Molecular Identification of Two Species of Saprolegnia that Predominant in Diwaniyah River/Iraq and Studying Them Nutrition Preference - Majid Kadhim Alshibly (Journal of Global Pharma Technology, 2017)
This study including isolation and identification the Saprolegniaspp from Diwaniyah river waters via baiting method, waters samples were collected during September and November of 2016, the identification was confirmed by polymers chain reaction (PCR). The nutrition preference of isolated fungi was tested by using standard bites (seeds of millet) which compared with other nutrients such as yellow and red corn seeds, sesame seeds, mung bean seeds and alfalfa seeds, the nutrition preference test were experimented by baiting method and also on solid and liquid cultures. The results showed that two species of Saprolegnia were isolated from waters of Diwaniyah River S. ferax and S. parasitica the first one appeared in 14 isolates (61%) and the second appeared in 8 isolates (39%). The nutrition preference test showed that the red corn was the best in attraction and growing Saprolegnia spp., this results indicate that the ability to use it in preparation media to isolate this fungi.Keywords: S. ferax , S.prasitica , PCR, Nutrition preference, Seeds.